Sleep quality and body weight status of Malaysian university students - Suhaimi, Nurul Fareeza; Ibrahim, Zuriati; Adznam, Siti Nur ‘Asyura; Md Noor, Sabariah (Nutrition Society of Malaysia, 2020)
Introduction: Inadequate sleep duration is a modifiable behaviour linked with body weight, yet limited is known on the role of sleep quality with body weight status among university students. The study aimed to determine sleep quality and its association with body weight status among university students. Methods: A crosssectional study was conducted among 240 university students (24.6% males, 75.4% females) with a mean age of 21.22±1.24 years. Subjects were recruited from four faculties of University Putra Malaysia (UPM). Information on socio-demographic, sleep quality and anthropometric measurements were collected. Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality, whereby a summation score from seven components yielded a global score on sleep quality, with higher scores indicating poor sleep quality. Results: Majority of subjects were Malay (79.2%) with a mean body mass index of 22.6kg/m2. A majority (61.3%) had normal body weight, with the prevalences of underweight (UW), overweight (OW), and obesity (OB) at 12.9%, 19.6% and 6.3%, respectively. The mean global PSQI score was 5.76±2.64, with half of the respondents (50.4%) experiencing poor sleep quality. OW-OB experienced poorer sleep quality (6.53±2.79, p=0.004) and longer sleep latency (1.34±0.10, p=0.008) relative to UW-NW. OB subjects had substantially more frequent sleep disturbances compared to non-OB subjects (1.53±0.64, p=0.012). Conclusion: Findings suggest that OW-OB students at university are at a greater risk of having reduced sleep quality with longer sleep latency and frequent sleep disturbances. There is a need for a wellness initiative to reduce the incidence of obesity while fostering healthier sleeping habits among university students.